An Assessment of the Impact of Preservation Processes on Fruit Juice Quality - Popek, Stanisław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
In the light of increasing consumer awareness of the relationship between food, nutrition, and health, the present work looks at the impact of one of the elements of thermal preservation on the determinants of juice quality. The impact on the juice is not limited only to extended product life but also to increased or decreased quality. This study has allowed the author to verify the hypothesis that the level of selected physicochemical and sensory determinants of quality of fruit juices depends on the type of preservation process used. The research was done on orange juices preserved using conventional and gentle pasteurisation. The results show the impact the individual preservation processes had on the sensory qualities of the juices under consideration.